2020
DOI: 10.1186/s13073-020-00784-9
|View full text |Cite
|
Sign up to set email alerts
|

The aging mouse microbiome has obesogenic characteristics

Abstract: Background During aging, there is a physiological decline, an increase of morbidity and mortality, and a natural change in the gut microbiome. In this study, we investigated the influence of the gut microbiome on different metabolic parameters in adult and aged mice. Methods Fecal and blood samples from adult (n = 42, 100–300 days) and aging (n = 32, 550–750 days) mice were collected. Microbiome analysis was done using QIIME2. Mouse weight and body composition were measured using NMR, and insulin and leptin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 41 publications
5
28
1
Order By: Relevance
“…Gut microbiota have been shown to regulate body fat content in mice [ 11 ] and are regarded as a putative target for obesity treatments [ 47 ]. As shown in the present study, HFD-driven obesity suppresses Bacteroidetes in the gut of mice ( Figure 3 C), an effect also observed in aging mice [ 49 ]. Moreover, HFD-driven obesity was found to increase the Firmicutes to Bacteroidetes ratio in the gut ( Figure 3 C), expanding on previous studies in genetically engineered obese mice and obese humans [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 83%
“…Gut microbiota have been shown to regulate body fat content in mice [ 11 ] and are regarded as a putative target for obesity treatments [ 47 ]. As shown in the present study, HFD-driven obesity suppresses Bacteroidetes in the gut of mice ( Figure 3 C), an effect also observed in aging mice [ 49 ]. Moreover, HFD-driven obesity was found to increase the Firmicutes to Bacteroidetes ratio in the gut ( Figure 3 C), expanding on previous studies in genetically engineered obese mice and obese humans [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 83%
“…As the murine microbiota could be influenced by various factors inherent to animals or the environment, we first studied and showed that caecal microbial composition of the immunocompetent or immunocompromised mice groups in our study were not confounded by experimental variables such as housing cages, dates of experimental procedures, gender, or age. The effect of age, especially, has been strongly linked to an altered gut microbiota (32)(33)(34)(35)(36). This has been discussed and illustrated further in Supplementary Results, Supplementary Figure 2, and Supplementary Table 1.…”
Section: De Novo Clustering Of Caecal Microbial Composition Clearly D...mentioning
confidence: 81%
“…A proportionately successive age category between 3-6 months, considered as adults (28), was chosen to mitigate any potential confounding effect of ageing in our immunodeficient mouse strains. This is because immunodeficiency causes differential ageing (29)(30)(31), and ageing is strongly linked to an altered gut microbiota profile (32)(33)(34)(35)(36). As no effect of ageing is known for NOD scid gamma mice (n = 26 mice; NSG, NOD.Cg-Prkdc scid Il2rg tm1Wjl /SzJ, JAX) that is one of the most immunocompromised mouse strains known so far, we studied two age groups of 3-6 months (n = 19) and of 10 months (n = 7).…”
Section: Animals and Housingmentioning
confidence: 99%
“…A previous study has shown that enhanced intestinal abundance of Adlercreutzia is associated with inflammation-induced depressive-like behaviour in mice [ 105 ]. Increased expression of the genus Dehalobacterium in mice is associated with ageing and food intervention-induced anti-inflammatory effects [ 106 , 107 ]. Moreover, reduced levels of intestinal Dehalobacterium observed in BTBR mice that have an autistic phenotype are associated with enhanced marble burying [ 108 ].…”
Section: Discussionmentioning
confidence: 99%